Attack of the evil minions! - Mayer, Kirsten; Daurio, Ken; Miller, Edward 1964-; Paul, Cinco (New York Boston Little, Brown, 2013)
El Macho starts kidnapping minions and uses purple goo to turn them into evil creatures, until the former supervillain Gru comes up with a way to turn them back
"Based on the motion picture screenplay by Cinco Paul & Ken Daurio."
At head of title: Despicable Me 2
2 13
Keywords: Despicable me 2 (Motion picture) -- Juvenile fiction; Good and evil -- Juvenile fiction; Jelly -- Juvenile fiction; Good and evil -- Fiction; Jelly -- Fiction; Children's stories; Movie novels